Optimisation of COVID‐19 diagnostic pathways in acute hospital admissions to prevent nosocomial transmission. (3rd August 2022) - Livingstone, Robert; Woodhead, Alexander; Bhandari, Megha; Dias, James; Smith, Trevor; Havelock, Tom; Stammers, Matthew
Abstract: Introduction: In the management of acute hospital admissions during the COVID‐19 pandemic, safe patient cohorting depends on robust admission diagnostic strategies. It is essential that screening strategies are sensitive and rapid, to prevent nosocomial transmission of COVID‐19 and maintain patient flow. Methods: We retrospectively identified all COVID‐19 positive and suspected cases at our institution screened by reverse transcription polymerase chain reaction (RT‐PCR) between 4 April and 28 June 2020. Using RT‐PCR positivity within 7 days as our reference standard, we assessed sensitivity and net‐benefit of three admission screening strategies: single admission RT‐PCR, composite admission RT‐PCR and CXR and repeat RT‐PCR with 48 h. Results: RT‐PCR single‐test sensitivity was 91.5% (87.8%–94.4%) versus 97.7% (95.4%–99.1%) ( p = 0.025) for RT‐PCR/CXR composite testing and 95.1% (92.1%–97.2%) ( p = 0.03) for repeated RT‐PCR. Net‐benefit was 0.83 for single RT‐PCR versus 0.89 for RT‐PCR/CXR and 0.87 for repeated RT‐PCR at 0.02% threshold probability. Conclusion: The RT‐PCR/CXR composite testing strategy was highly sensitive when screening patients at the point of hospital admission. Real‐world sensitivity of this approach was comparable to repeat RT‐PCR testing within 48 h; however, faster facilitating improved patient flow. Abstract : RT‐PCR/CXR composite testing was highly sensitive when screening patients at the point of hospital admission for COVID‐19 infection. Real‐world sensitivity of this approach was comparable to repeat RT‐PCR testing within 48 h; however, faster facilitating improved patient flow.